Antioxidant activity and bioactive compounds of lettuce improved by espresso coffee residues - Cruz, Rebeca (2013)
The antioxidant activity and individual bioactive compounds of lettuce, cultivated with 2.5–30% (v/v) of fresh or composted espresso spent coffee grounds, were assessed. A progressive enhancement of lettuce’s antioxidant capacity, evaluated by radical scavenging effect and reducing power, was exhibited with the increment of fresh spent coffee amounts, while this pattern was not so clear with composted treatments. Total reducing capacity also improved, particularly for low spent coffee concentrations. Additionally, very significant positive correlations were observed for all carotenoids in plants from fresh spent coffee treatments, particularly for violaxanthin, evaluated by HPLC. Furthermore, chlorophyll a was a good discriminating factor between control group and all spent coffee treated samples, while vitamin E was not significantly affected. Espresso spent coffee grounds are a recognised and valuable source of bioactive compounds, proving herein, for the first time, to potentiate the antioxidant pool and quality of the vegetables produced.